Morphological regularities of low-frequency signal due to solar flare events at low-latitude region / Afifah Taat - TaaT, Afifah (2018)
Solar flare is one of the main phenomena of space weather that has affected technologies such as radio communication, satellite systems and power grid operations. The interaction process has led to the variations of frequencies which can be observed from the ground station. This research focuses mainly on low frequencies which are Very Low Frequency (VLF) and Ultra-Low Frequency (ULF) within the range of 3 - 30kHz and 1.7-500 mHz respectively. The affected frequency variations were observed during quiet (Q-day) and flare (F-day) day of solar cycle 24. The recorded data of the VLF and ULF signals were extracted from the Atmospheric Weather Electromagnetic System for Observation Modelling and Education (AWESOME) located at Universiti Kebangsaan Malaysia (UKM) and the Magnetic Data Acquisition System (MAGDAS) respectively. Previous researchers have demonstrated the affected frequencies mainly due to geomagnetic storms instead of solar flare events and separately discussed between the frequencies. In contrast, the new method of analysis due to solar flare events at lowlatitude region was presented in this research. The combination investigation and observation have been done for both VLF and ULF signals. The modeling of Long Wave Propagation Capability (LWPC) code and International Reference Ionosphere Model (IRI2016) were applied to generate the values of Ne (electron density, m־ᶟ), H7(VLF reflection height parameter, km) and β (exponential sharpness factor, km־¹). In addition to that, the geomagnetic field components (H and Z) were calculated to observe the correlation of ULF variations associated with solar flare events. In the analysis, the diurnal variations of VLF and ULF signals have been observed. Q-day was selected to measure the Average Amplitude Difference (AAD) for ULF while the method of Average Percentage Difference (APD) has been used for VLF signal during daytime and nighttime for three (3) different transmitter stations which are NWC/19.8kHz, JJI/ 22.2kHz, and DHO/23.4kHz.All the transmitters had different latitudes and distances from the receiver stations (UKM) and propagated within the Earth-ionosphere waveguide (EIWG). It is found that, the NWC signal had lower APD which was 7.72% as compared to JJI (10.14%) and DHO (15.4%). For further investigation on lowfrequency signals (VLF and ULF), the affected amplitude (AA) due to solar flares demonstrated different classes of solar fluxes which are C, M, and X-Class.